The Potential of Glass Waste as Sand Replacement in Concrete Mix for 3DCP Technology - Zaidi, Muhamad Aniq Haziq; Kasim, Narimah; Idi Namara (Journal of Sustainable Materials Processing and Management, 2024)
The global population generates millions of metric tons of waste glass annually, with only a small fraction being recycled, leaving the rest to accumulate in stockpiles. This underutilization of waste glass poses environmental concerns. Although waste glass has been utilized in the construction industry for decades, there is an urgent need to increase recycling efforts to address sustainability concerns. In parallel, the construction sector has seen the emergence of 3D Construction Printing (3DCP) technology, which presents innovative opportunities. However, current research in 3DCP predominantly focuses on conventional methods, with limited attention given to environmentally sustainable practices, particularly concerning concrete production. This study aims to bridge this gap by investigating the potential of waste glass as sand replacement in the concrete mixture for 3DCP. Therefore, the objectives of the study are to determine the optimal proportion of waste glass to be used as a sand replacement in 3DCP and to assess the resulting concrete's strength. Furthermore, it investigates the acceptance of waste glass as a viable sand replacement in 3DCP. The research involves varying levels of waste glass (0%, 10%, 15%, 20%, and 25%) as a partial substitute for sand in concrete mixtures. In addition to quantitative analysis, this study employs qualitative methods, such as interviews with industries, which is consultant and developer company, to gauge the acceptance and feasibility of waste glass as a sand replacement in 3D construction printing. The findings from this research can potentially encourage the widespread adoption of waste glass as a sustainable alternative, reducing waste disposal costs, mitigating environmental pollution risks, and conserving valuable landfill space. Ultimately, this study contributes to the promotion of green concrete practices and aligns with the Sustainable Development Goals (SDG).